Sorption and desorption studies of radioiodine onto silver chloride via batch equilibration with its aqueous media. (December 2015) - Mostafa, M.; Ramadan, H.E.; El-Amir, M.A.
Abstract: The uncontrolled spread out of radioiodine (especially 1 3 1 I) produced from nuclear activities or accidents, due to its high volatility, to the biosphere represents an environmental impact because of its concentration in the thyroid gland and accumulation on soil surface. This work represents a simple method for isolation of radioiodine from aqueous solution in the form of insoluble solid compound and further recovery of it in aqueous phase for any further controlled use. Crystalline silver chloride was prepared and characterized. Batch sorption of 131 I onto the prepared AgCl was studied from different aqueous media (H2 O and NaOH of different concentrations) and at different I − :Ag molar ratios (from alkaline media) for different times at 25 °C. It was found that the sorption yield of 131 I from 2.5 M NaOH solution (at I − :Ag and S2 O3 2− :I − molar ratios of 0.025 and 2, respectively) reached 97.7% after 6 h and only slightly increased to 98.6% after 16 h of contact time. The presence of H2 O2 adversely affected the batch sorption process. The included REDOX and precipitation reactions were discussed. Batch desorption of the sorbed 131 I from AgCl into aqueous phase was studied with NaOCl solutions of different concentrations and different contact times at 25 °C. Desorption yield of 131 I was found to be 94.5% with 10 mL of 0.5 M NaOCl solution after contact time of 16 h. Kinetic analysis has been performed for both batch sorption and desorption processes. Graphical abstract: Highlights: Crystalline AgCl was prepared via a simple method and characterized. Batch sorption and desorption of 131 I onto and from AgCl particles was studied. Kinetic analysis was conducted for both sorption and desorption processes.